Essays in household finance - Vihriälä, EJ (2020)
This thesis contains three essays on household finance focusing on household consumption and savings decisions. The first paper studies household demand for flexibility in debt repayment. Based on evidence from a natural experiment, I find that few households apply for flexibility in debt repayment, although all households weakly prefer flexibility in a standard consumption- savings model. The paper studies how self-control problems and a desire for commitment, as well as inattention and inertia can explain observed household behavior. The second paper untangles reasons for the credit card debt puzzle describing the co-holding of high-cost debt and low-yield assets. I test existing theories for co-holding and provide evidence on the contribution to co-holding of intra-household financial pooling and of anchoring to minimum credit card payments. The final paper studies household heterogeneity in insuring against cohort-level earnings shocks using: (i) investment income flows; (ii) the tax-and-transfer-system; and (iii) credit markets. The insurance mechanisms vary by household socio-economic characteristics captured by housing tenure.